Tietze syndrome - Gedik, İsmail Ertuğrul and Alar, Timuçin (Journal of Surgery and Medicine, 2020)
Tietze syndrome, first described in 1921 by Prof. Alexander TIETZE, is characterized with tender nonsuppurative swelling, pain, and tissue edema in the second or third costosternal cartilage. Differential diagnosis of Tietze syndrome includes diverse diseases, and its diagnosis relies on clinical examination, not the use of additional diagnostic techniques. The treatment of Tietze syndrome includes the use of anti-inflammatory medication and implementation of lifestyle modifications during the attacks. Surgical treatment is reserved for refractory cases and often is not necessary. Tietze syndrome can easily be diagnosed and treated in primary care medicine practice due to its benign nature.